A scanning electron microscopic study of the patterns of external root resorption under different conditions - Sreeja, Ravindran; Minal, Chaudhary; Madhuri, Tumsare; Swati, Patil; Vijay, Wadhwan (Journal of Applied Oral Science, 2009)
OBJECTIVE: The aim of this study was to examine if there are qualitative differences in the appearance of external root resorption patterns of primary teeth undergoing physiologic resorption and permanent teeth undergoing pathological root resorption in different conditions. MATERIAL AND METHODS: A total of 40 teeth undergoing external root resorption in different conditions were divided into 4 groups and prepared for examination under scanning electron microscopy at magnifications ranging from 20x to 1000x. Group I: 10 primary molars exfoliated due to physiologic root resorption; Group II: 10 permanent teeth with periapical granulomas showing signs of resorption; Group III:10 permanent teeth therapeutically extracted during the course of orthodontic therapy with evidence of resorption, and Group IV: 10 permanent teeth associated with odontogenic tumors that showed evidence of resorption. RESULTS: In Group I, the primary teeth undergoing resorption showed smooth extensive and predominantly regular areas reflecting the slow ongoing physiologic process. In Group II, the teeth with periapical granulomas showed the resorption was localized to apex with a funnel shaped appearance in most cases. Teeth in Group III, which had been subjected to a short period of light orthodontic force, showed the presence of numerous resorption craters with adjoining areas of cemental repair in some cases. Teeth associated with odontogenic tumors in Group IV showed many variations in the patterns of resorption with extensive loss of root length and a sharp cut appearance of the root in most cases. CONCLUSION: Differences were observed in the patterns of external root resorption among the studied groups of primary and permanent teeth under physiologic and pathological conditions.